An Analysis of Languagae Disorder in “Fly Away” (2011) Movie - Eva Meidi Kulsum; Aliya Nurdayani; Ayang Winda Sri Widianingsih; Rina Mutiarawati (UIN Sunan Gunung Djati Bandung, 2024)
Language disorder is the most frequent developmental disorder in childhood and it has a significant negative impact on children’s development. There are several types of language disorders that can be detected early, one of them is autism. This study aims to examine language disorder in a movie which focuses on one of the characters that shows Autism-Spectrum Disorder (ASD) symptoms. The method used in this research is qualitative analysis method by collecting data through movies. This study analysis was conducted on Mandy's character in the movie